VARIABEL-VARIABEL YANG MEMPENGARUHI KINERJA PADA PERUSAHAAN-PERUSAHAAN DI INDONESIA - Chandra Suwondo (Institut Bisnis dan Multimedia asmi, 2015)
Whereas many other variables that can affect and improve performance (according to Armstrong) are ones involving Individual Factor, Leadership Factor, Working Group Factor, System Factor and Situation Factor. Applying particularly to enterprises in Indonesia, Performance Variables (Dependent Variable) influenced by Independent Variable are given as: